ANALISIS STATUS EKSPLOITASI SUMBERDAYA PERIKANAN PROVINSI ACEH - Asmawati Asmawati; Muhammad Nasir (Center for Research and Community Service (LPPM) University of Abulyatama, 2017)
Fish commodities are a renewable resource and public property, whose utilization needs to be sustainable. This study aims to analyze the condition of the utilization of Aceh fishery resources, using a simple method of long-term fish supply curve, by assessing the relationship between production and price movement of fish. The 27-year time series data published by DKP has been used, in the form of production and price data. The results of the analysis indicate that the utilization has excessive exploitation for Malacca Strait fisheries, and less exploitation in the Indian Ocean region